STUDENT CREATED VIDEOS IN ENGLISH LANGUAGE TEACHING - I. E. ABRAMOVA; O. M. SHEREKHOVA; E. P. SHISHMOLINA (Высшее образование в России)
Student filmmaking technology is not widespread in the EFL teaching scenario at Russian Universities whereas it has been successfully implemented in different subject areas and at different study levels in other countries. The article focuses on practical application of such a technology innovation as student filmmaking to the foreign language learning process. It also describes the project development stages and the assessment criteria used. Creative profession-oriented projects of this type increase students’ motivation, encourage them to learn the English language and use it in academic or professional settings.